Improving Cure Rates in Onychomycosis. Issue 6 (November 2016) - Gupta, Aditya K.; Cernea, Maria; Foley, Kelly A.
Background: Onychomycosis is a persistent fungal nail infection that is notoriously hard to treat. Approximately 20% to 25% of patients with onychomycosis do not respond to treatment, and 10% to 53% of patients relapse. As such, successful treatment is imperative for long-term disease management. Objective: To identify ways to improve cure rates for onychomycosis. Method: The literature on onychomycosis treatment and recurrence was reviewed to summarize treatment approaches and suggest strategies to increase cure rates. Results and Conclusion: To improve treatment success in onychomycosis, we suggest the following measures be followed: (1) onychomycosis must be correctly diagnosed, (2) the treatment regimen should be tailored to the individual patient, (3) the efficacy of antifungals must be maximized, and (4) recurrence must be prevented.